Usage of Track Link Dynamic Motion Simulation - Chalupa, Milan; Veverka, Josef; Vlach, Radek (Manufacturing Technology Journal, 2014)
The article describes mathematical model and possible usage of results of dynamic loading simulation of the chassis of track vehicle. The computational model is designed for computational simulating system MSC.ADAMS.AVT. Possibilities of research results usage are described in the article mainly. Results of simulation calculations were used for make-up of constructional parameters parts file of vehicle chassis and findings of influence their changes on changes of directional vehicle stability by running at first. Make - up of approximate relations for transaction of fast orientation calculations is second described possibility of results simulation calculations usage. The possibility of usage of results simulation to do verification of mathematical model is third possibility of usage results simulation calculations. The optimization of influence changes of several design value together is fourth possibility of usage of results simulation calculations that is described in this article.
Keywords: dynamic properties simulation; computation modeling